If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6f + 9 = 0 Reorder the terms: 9 + 6f = 0 Solving 9 + 6f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 6f = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 6f = 0 + -9 6f = 0 + -9 Combine like terms: 0 + -9 = -9 6f = -9 Divide each side by '6'. f = -1.5 Simplifying f = -1.5
| -8x=-3 | | 5a+8=6a-4 | | x^2y=y^3 | | -7c+9=e+1 | | x-4+5=7 | | y+3y+y-7=19.90 | | 3x+22=5x | | 9h-8=55 | | (x*40)+(x*6.75)+(x*3.5)=502.5 | | X+6x-97=0 | | 4x^2-44x+110=0 | | a^2+a=3 | | 10000*0.08*5=x | | 2(1x-3)-4=12 | | =0.6m+30 | | -6x^2-13x+28=0 | | =-4800t+52800 | | 0=-10x^2+3500x-250000 | | -6x^2-13x=28 | | -6x^2-13x=12 | | -6x^2-13x=128 | | 3x(x-4)+x=-2 | | 196.60=1.7x | | 196.60=x+7x | | 2x+75=1x+18 | | 12x^2+34x=-24 | | 30+2x=-2(-3-4x) | | 2x+75=1x | | 1.07x=192.60 | | x=.6*180 | | -5(3-q)+4= | | 8h+5=61 |